An In Vitro Barrier Model of the Human Submandibular Salivary Gland Epithelium Based on a Single Cell Clone of Cell Line HTB-41: Establishment and Application for Biomarker Transport Studies - Lin, Grace C. (Biomedicines, 2020)
The blood–saliva barrier (BSB) consists of the sum of the epithelial cell layers of the oral mucosa and salivary glands. In vitro models of the BSB are inevitable to investigate and understand the transport of salivary biomarkers from blood to saliva. Up to now, standardized, cell line-based models of the epithelium of the submandibular salivary gland are still missing for this purpose. Therefore, we established epithelial barrier models of the submandibular gland derived from human cell line HTB-41 (A-253). Single clone isolation resulted in five different clones (B2, B4, B9, D3, and F11). Clones were compared to the parental cell line HTB-41 using measurements of the transepithelial electrical resistance (TEER), paracellular marker permeability assays and analysis of marker expression for acinar, ductal, and myoepithelial cells. Two clones (B9, D3) were characterized to be of acinar origin, one clone (F11) to be of myoepithelial origin and one isolation (B4) derived from two cells, to be presumably a mixture of acinar and ductal origin. Clone B2, presumably of ductal origin, showed a significantly higher paracellular barrier compared to other clones and parental HTB-41. The distinct molecular identity of clone B2 was confirmed by immunofluorescent staining, qPCR, and flow cytometry. Experiments with ferritin, a biomarker for iron storage, demonstrated the applicability of the selected model based on clone B2 for transport studies. In conclusion, five different clones originating from the submandibular gland cell line HTB-41 were successfully characterized and established as epithelial barrier models. Studies with the model based on the tightest clone B2 confirmed its suitability for transport studies in biomarker research.